Inclusion of indigenous and ethnic minority populations in intervention trials: challenges and strategies in a New Zealand supermarket study. Issue 10 (1st July 2009) - Mhurchu, C Ni; Blakely, T; Funaki-Tahifote, M; McKerchar, C; Wilton, J; Chua, S; Jiang, Y
Abstract : Background: The Supermarket Healthy Options Project (SHOP) is a large, randomised, controlled trial designed to evaluate the effect of tailored nutrition education and price discounts on supermarket food purchases. A key objective was to recruit approximately equal numbers of Māori, Pacific and non-Māori, non-Pacific shoppers. This paper describes the recruitment strategies used and evaluates their impact on recruitment of Māori, Pacific and non-Māori, non-Pacific trial participants. Methods: Trial recruitment strategies included mailed invitations to an electronic register of supermarket customers; in-store targeted recruitment; and community-based recruitment. Results: Of the 1103 total trial randomisations for whom ethnicity was known, 247 (22%) were Māori, 101 (9%) Pacific and 755 (68%) were non-Māori, non-Pacific shoppers. Mailed invitations produced the greatest proportion of randomisations (73% vs 7% in-store, and 20% from community recruitment). However, in-store and community recruitment were essential to boost Māori and Pacific samples. The cost of mailout (NZ40 (£14) per randomised participant) was considerably less than the cost of community and in-store recruitment (NZ301 (£105) per randomised participant). Conclusions: The findings demonstrate considerable challenges and cost in recruiting indigenous and minority ethnic participants into intervention trials. Researchers and funding organisations should allocate more resources to recruitment of indigenous and minority populations than to recruitment of majority populations. Community recruitment and networks appear to be better ways to recruit these populations than passive strategies like mailouts.